Kebijakan Ekstrakurikuler Pramuka: Analisis Sentimen di Instagram & Tiktok dengan Metode Naïve Bayes Classifier - Mustaqim, Mujahidil (Nusa Putra University, 2024)
In 2024, a new regulation was issued by the government through Permendikbud number 12 of 2024. One of the important points of the policy that was widely highlighted by the public on social media was that extracurricular scouting activities became optional activities that could be followed by students at the Elementary and Secondary Education levels. This article was written using the sentiment analysis research method using the nvivo application and the Naïve Bayes Classifier (NBC) analysis technique. The study was conducted on 1000 correspondents divided into 500 correspondents on Instagram and 500 on TikTok. The study revealed a number of scientific facts, namely First, as many as 73% of people on Instagram gave negative responses and were validated by 94% of people's responses on TikTok which also gave negative responses. Second, the dominant emotion expressed by people on social media was angry sentiment, as many as 49% of people on Instagram and 67% on TikTok. Third, the results of the NBC sentiment analysis found that the highest probability was in the negative sentiment category of 0.0191